Prevalence and clinical prediction of mitochondrial disorders in a large neuropediatric cohort. Issue 6 (19th September 2021) - van der Ven, Amelie T.; Johannsen, Jessika; Kortüm, Fanny; Wagner, Matias; Tsiakas, Konstantinos; Bierhals, Tatjana; Lessel, Davor; Herget, Theresia; Kloth, Katja; Lisfeld, Jasmin; Scholz, Tasja; Obi, Nadia; et al.
Abstract: Neurological symptoms are frequent and often a leading feature of childhood‐onset mitochondrial disorders (MD) but the exact incidence of MD in unselected neuropediatric patients is unknown. Their early detection is desirable due to a potentially rapid clinical decline and the availability of management options. In 491 children with neurological symptoms, a comprehensive diagnostic work‐up including exome sequencing was performed. The success rate in terms of a molecular genetic diagnosis within our cohort was 51%. Disease‐causing variants in a mitochondria‐associated gene were detected in 12% of solved cases. In order to facilitate the clinical identification of MDs within neuropediatric cohorts, we have created an easy‐to‐use bedside‐tool, the MDC‐NP. In our cohort, the MDC‐NP predicted disease conditions related to MDs with a sensitivity of 0.83, and a specificity of 0.96. Abstract : We provide an easy to use bed‐side screening tool for the clinical identification of mitochondrial diseases in neuropediatric patients